ANALISIS KARAKTERISTIK PERUSAHAAN DAN ENVIRONMENTAL PERFORMANCE TERHADAP ENVIRONMENTAL DISCLOSURE - Purnama, Dendi (Jurnal Riset Keuangan dan Akuntansi, 2018)
This study aims to analyze the effect of profitability, leverage, company size, and environmental performance to environmental disclosure. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2014 until 2016. The sample in this study were 71 companies for 3 years. The method of analysis used in this study is multiple regression analysis.The results show that profitability and leverage have no effect on environmental disclosure, while firm size and environmental performance have positive effect on environmental disclosure. Taken together, the variables of profitability, leverage, firm size and environmental performance have significant effect on environmental disclosure.Â Â Keywords: Profitability; Leverage; Size; Environmental Performance; Environmental Disclosure